Supply chain innovations for additive manufacturing. Issue 1 (20th December 2019) - Luomaranta, Toni; Martinsuo, Miia
Abstract : Purpose: Additive manufacturing (AM) involves the renewal of production systems and also has implications for firms' supply chains. Innovations related to AM supply chains are, so far, insufficiently understood, but their success will require firms' awareness of their systemic nature and their firm-specific implications. The purpose of this paper is to explore the supply chain innovations dealing with AM in business-to-business supply chains. Design/methodology/approach: An exploratory qualitative research design is used. Interviews were conducted in 20 firms, workshops were organized to map AM-related processes and activities, and supply chain innovations were analyzed. Findings: This study reveals practical changes in supply chains and requirements for AM-related supply chain innovations. While earlier research has centered on technology or firm-specific AM implementations, this study shows that fully leveraging AM will require innovations at the level of the supply chain, including innovations in business processes, technology and structure, as well as supportive changes in the business environment. These innovations occur in different parts of the AM supply chain and are emphasized differently within different firm types. Research limitations/implications: This research was conducted in one country in the context of the machine building and process industry with a limited data set, which limits the generalizability of the results. The results offer an analytical framework and identify new research avenues for exploring the innovations in partial or complete AM supply chains. Practical implications: The results offer a framework to assess the current state and future needs in AM-related supply chain innovations. Practical ideas are proposed to enhance AM adoption throughout firms' supply chains. These results are important to managers because they can help them position their firms and guide the activities and collaborations with other firms in the AM supply chain. Originality/value: This study draws attention to the supply chain innovations required when firms adopt AM in their processes. The generic supply chain innovation framework is enhanced by adding the business context as a necessary component. Implementation of AM is shown to depend on the context both at the level of the supply chain and the firm's unique role in the supply chain. The holistic view taken reveals that successful AM technology adoption requires broad involvement from different firms across the supply chain.